An Algorithm for Tracking the Position and Velocity of Multiple Neuronal Signals Using Implantable Microelectrodes In Vivo - Lionel M. Broche (MDPI AG, 2021)
Increasingly complex multi-electrode arrays for the study of neurons both in vitro and in vivo have been developed with the aim of tracking the conduction of neural action potentials across a complex interconnected network. This is usually performed through the use of electrodes to record from single or small groups of microelectrodes, and using only one electrode to monitor an action potential at any given time. More complex high-density electrode structures (with thousands of electrodes or more) capable of tracking action potential propagation have been developed but are not widely available. We have developed an algorithm taking data from clusters of electrodes positioned such that action potentials are detected by multiple sites, and using this to detect the location and velocity of action potentials from multiple neurons. The system has been tested by analyzing recordings from probes implanted into the locust nervous system, where recorded positions and velocities correlate well with the known physical form of the nerve.